Integrasi Blockchain dan Algoritma Kriptografi Untuk Perlindungan Data Pribadi: Tinjauan Literatur Sistematis 2021- 2025 - Mubarak, Roy; Riadi, Imam; Sutikno, Tole (Institut Informatika Dan Bisnis Darmajaya, 2025)
Personal data has become a highly valuable asset in the rapidly evolving digital era. However, the increasing reliance on digital technology also poses serious cybersecurity threats, including data breaches, hacking, and misuse of personal information. Increasingly frequent data leaks in social media applications, e-wallets, and ecommerce platforms highlight the urgency of protecting user privacy. Despite the implementation of stricter regulations such as the GDPR in Europe and the Personal Data Protection Act (PDPA) in Indonesia, personal data security remains a significant challenge. This study aims to identify and analyse variables that contribute to improving personal data security amidst cyber threats in the digital era. The variables examined include: objects, frameworks, methods, and tools used. The approach used in this study was a systematic literature review using the PRISMA method, which examined 85 papers from three major databases (Google Scholar, IEEE, and Springer) between 2021 and 2025. The results show a trend of integrating blockchain technology with cryptography, smart contracts, and artificial intelligence to strengthen personal data protection and ensure compliance with global privacy regulations. This research concludes that blockchain has significant potential to address cyber threats and could become an innovative solution for future personal data protection. This article also outlines current research contributions and the development direction needed in the field of blockchain-based data security and cryptographic techniques.